THE LECTURE SYSTEM IN ELEMENTARY ACCOUNTING. - Mead, Stuart B.; Ruswinckel, John W. (The Accounting Review, 1959)
This article focuses on the lecture system in elementary accounting. The lecture system has been used for many years in elementary accounting courses, especially when a large number of recitation sections are involved. If comparable coverage and results are to be obtained in a course enrolling many students and composed of numerous sections, coordination of the course appears necessary. The lecture system seems to be the most satisfactory method of attaining the degree of coordination desired. Although the lecture hour can become subject to misuse, it should be used to introduce subject matter, to discuss controversial points, to aid in the development of more difficult concepts and principles, to review material already covered, and for the purpose of examinations. Examinations in a multi-section course can become a disagreeable task to an instructor teaching several sections, as well as a source of inequity from the viewpoint of the student. The advantage of the so-called departmental examination given under the lecture system is the fact that all students in a lecture group take the same test.